Phynotypic and genotypic identification of Eimeria species in backyard chicken in Nineveh governorate, Iraq - Adnan M. Ahmed; Haitham S. AlBakri (Iraqi Journal of Veterinary Sciences, 2021)
Coccidiosis is an intestinal disease caused by a parasite of the genus Eimeria. This parasite mainly affects poultry species and causes great economic losses in the poultry industry. This study was designed to estimate the prevalence of coccidiosis in the local breed of domestic chicken in Nineveh Governorate, Iraq. 450 faecal swabs and intestinal samples (intestinal scraping) were collected from different local breeds of home-bred chickens from October 2020 to the end of March 2021. All fecal samples were examined using the flotation method by using sugar solution, and Eimeria was confirmed by the polymerase chain reaction method. Fecal examination results showed that 32.6% of the total samples were positive for Eimeria oocysts, classified into six species including E. brunetti, E. mitis.E. maxima E. acervulina E. necatrix, E. tenella with infection rates are 57.5, 44.2, 42.1, 26.5, 20.4, 16.3%, respectively. The phenotypic results were genetically confirmed by the result of the reaction of 455 base pairs. The prevalence of coccidiosis was highest in chickens less than three months of age 49.2% and lowest in chickens older than 6 months 23.9%